A Mediating- Moderating Model on Job Stress and Emotional Intelligence (KASBIT Business Journal, 2021)
Job stress has adverse consequences on organizations and employees. Given its importance, we have developed a conceptual framework that has seven direct and three moderating relationships. We have focused on SMEs in Karachi, as it significantly contributes towards employment generation and GDP. Based on self-administered questionnaires, we have collected the data from lower and middle management levels of SMEs. Due to the non-availability of the sample frame, we have used convenience sampling. We distributed 490 questionnaires and received 470 questionnaires, acceptable in studies with a large sample size. The study has used Smart PLS Version 2.3 for statistical analysis. Our results suggest job stress negatively affects life satisfaction, happiness, and job performance. The study also found emotional intelligence promotes life satisfaction, reduces happiness, decreases job performance, and increases job stress. The results also suggest that emotional intelligence moderates life satisfaction, happiness, and job performance. The findings will help SMEs to reduce job-related stress. The study has used the mediating-moderating model, which brings insight into the discussed phenomena.
Keywords: Job stress; life satisfaction; happiness; job performance; emotional intelligence